Optimized Pt Single Atom Harvesting on TiO2 Nanotubes—Towards a Most Efficient Photocatalyst - Wu, Zhenni; Hwang, Imgon; Cha, Gi; Qin, Shanshan; Tomanec, Ondřej; Badura, Zdenek; Kment, Stepan; Zboril, Radek; Schmuki, Patrik (Small, 2021)
In the present work the authors show that anodic TiO2 nanotubes (NT) show excellent harvesting properties for Pt single atoms (Pt SAs) from highly dilute Pt solutions. The tube walls of anodic nanotubes, after adequate annealing to anatase, provide ample of suitable trapping sites—that is, surface Ti3+-Ov (Ov: oxygen vacancy) defects that are highly effective to extract and accumulate Pt in the form of SAs. A saturated (maximized) SA density can be achieved by an overnight immersion of a TiO2 NT layer to a H2PtCl6 solution with a concentration that is as low as 0.01 mm Pt. Such TiO2 NTs with surface trapped Pt SAs provide a maximized high activity for photocatalytic H2 generation (reaching a turnover frequency (TOF) of 1.24 × 106 h−1 at a density of 1.4 × 105 Pt atoms µm−2)—a higher loading with Pt nanoparticles does not further increase the photocatalytic activity. Overall, these findings show that anodic TiO2 nanotubes provide a remarkable substrate for Pt extraction and recovery from very dilute solutions that directly results in a highly efficient photocatalyst, fabricated by a simple immersion technique.
CRIS-Team Scopus Importer:2021-11-12
Keywords: dark deposition; hydrogen generation; photocatalysis; single-atom catalysis; TiO